PENGEMBANGAN HANDOUT TARI TOPENG GETAK UNTUK SISWA KELAS IV SEKOLAH DASAR - Harsiwi, Nova Estu; Perdana , Parrisca Indra (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Topeng Getak Dance has increasingly strengthened its position as the cultural identity of Pamekasan Regency after being designated as an Intangible Cultural Heritage in 2024. However, learning materials that incorporate Topeng Getak Dance as instructional content have not yet been developed in Pamekasan Regency. This study aimed to develop learning materials on Topeng Getak Dance of Pamekasan that are valid and practical for use in classroom learning activities. The developed handout is intended to support learning on cultural diversity in the local environment. This research employed a research and development approach using the 4D development model proposed by Thiagarajan. Due to limitations of time and cost, the dissemination stage was not implemented. The results indicate that the developed product in the form of a Topeng Getak Dance handout is valid and practical for instructional use. This is evidenced by the learning material expert validation result of 85% and the content expert validation result of 83%, both of which fall into the valid category. The average student response questionnaire score reached 87% in the limited trial and 87% in the development trial, while the teacher response questionnaire score in the development trial was 83.75%. These results indicate that the developed handout is categorized as practical